Sonocrystallization: For Better Pharmaceutical Crystals - VAMSI KRISHNA, M.; RAMESH BABU, J.; LATHA, P.V.M.; GOWRI SANKAR, D. (Asian Journal of Chemistry, 2010)
In recent years crystallization using ultrasound has received greater impetus in the pharmaceutical field. It provides an effective, versatile and non-invasive way of improving crystal properties. This technique can be used to crystallize complex organic molecules (most of them are drugs) that are difficult to crystallize by conventional techniques. Sonocrystallization can also eliminate the need to add seed crystals, which can be more advantageous in sterile operations. A combination of ultrasound and vortex mixing can be used to form micro particles, ideal for cost effective production of inhaled therapeutic agents. This article takes a detailed look at the sonocrystallization and the benefits that it can bring to the pharmaceutical industry.